Effects of COVID-19 pandemic on orthodontic practice - Alqahtani, Jamal Mohammad; Alanazi, Rawan Khaled; Edrees, Mustafa Burhan; Alaqla, Sara Abdulrahman; Alharbi, Shuruq Bandar; Amer, Orjuwan Mohammed; Aldrees, Shorouq Shaker; Almutairi, Abdulrahman Nashmi; Gahtani, Reyouf Osama Al; Alhassoun, Raghad Hassoun; Alharbi, Ibrahim Mohammed (International Journal Of Community Medicine And Public Health, 2022)
The COVID-19 is a respiratory illness which was declared as pandemic in 2020 by WHO. The pandemic has not only affected daily lives of people but greatly influenced the healthcare system across the globe especially dental care setup which was affected due to lockdown preventive measures taken by various countries. Orthodontic treatment involves regular consultations and visits to the dental clinic which unfortunately got negatively affected by the pandemic situation resulting in delayed appointments and prolonged treatment. The aim of this research was to review the available information regarding the effects of COVID-19 pandemic on orthodontic practice. Most of the orthodontic services were suspended and dental care settings were closed during the time of pandemic, only emergency patients were treated. Due to the delay in orthodontic services and treatment most orthodontic problems such as loosening brackets and arch wires could not be treated timely which affected patients. Many orthodontics utilized the digital technology for the provision of services and held virtual-based sessions with their patients. Findings from the literature exhibit that corona virus disease pandemic has posed a significant impact on the field of orthodontics however, in future more research is needed on designing management strategies in times of pandemic, so the dental care and orthodontic services are not affected.